IMPLEMENTASI DATA MINING MENGGUNAKAN METODE LEAST SQUARE UNTUK MEMPREDIKSI JUMLAH PENJUALAN MEBEL DI UD. MEBEL JATI - Sarwido, Sarwido; Shofi'in, Faiz Ali; Saputro, Heru (Jurnal Disprotek, 2023)
UD Mebel Teak is one of the many shops that provide furniture or household items such as chairs, sideboards, cupboards and so on. The amount of sales transaction data at UD Mebel Jati Stores is currently only used to make sales reports and stock items. In fact, from this sales data mining, it can be searched for an estimate of the amount of sales of an item for a certain month using a calculation method. From here, it can be seen the forecasting of the number of sales for a certain month so that the UD Teak Furniture Store can estimate the supply of furniture. The author will design a data mining implementation system to predict furniture sales using the least squares method to make better use of existing sales transaction data. The design will be implemented using the PHP programming language and MySql database. PHP is a programming language that integrates with HTML to create attractive web pages. This research is expected to produce a datamining implementation system to predict furniture sales using the website-based least squares method. This system is expected to be able to provide information about which furniture is in great demand by consumers in order to provide stock for that furniture. the results of the validation carried out by material experts on sales forecasting decision support systems contained 7 instruments, an ideal score of 63 with an expert score of 63 and a presentation of 100% was declared feasible. And from the verification of media experts from 9 instruments, it was declared feasible with an ideal score of 77 from an expert score of 79 and a presentation of 96.2%.